The Role of Education in Promoting Self-Care Behaviors in Patients with Hypertension: An Application of the PRECEDE Model - Marzeyeh Abedi; Mahboobe Borhani; Hasan Rahimzadeh; Ali Mehri; Zakieh Sadat Hoseini (Journal of Education and Community Health)
Aims: Hypertension is one of the most common chronic health problems worldwide and self-care behaviors are an important part of managing blood pressure in these patients. Therefore, the present study was conducted to determine the effect of educational intervention based on the PRECEDE model on the promotion of self-care behaviors of patients with hypertension. Materials & Methods: This randomized controlled trial was performed among 102 patients with hypertension who were selected by multi-stage cluster sampling in 2018. Data collection tools included demographic information and a standard questionnaire based on the PRECEDE model constructs which were completed by interview. The experimental group participated in 4 training sessions. Questionnaires were collected before and 3 months after the educational intervention from the participants of the experimental and control groups. Data were analyzed in SPSS 19 software using Chi-square, independent t-test, paired t-test, and linear regression. Findings: The results showed that knowledge, attitude and enabling factors predicted 20% of the variance of self-care behaviors of patients with hypertension before the educational intervention. After the educational intervention, the mean scores of all structures of the PRECEDE model were statistically significant between the experimental and control groups (p<0.05), except for the enabling factors (p>0.05). Also, the mean score of self-care behaviors 3 months after the educational intervention in the experimental group was significantly increased compared to the control group (p<0.05). Conclusions: Increasing the average of self-care behavior in patients undergoing educational intervention indicates the effective role of education in the use of self-care behaviors. Proper planning for educational interventions based on the PRECEDE model as well as providing the necessary structures is necessary to facilitate the realization of self-care behaviors in patients with hypertension.